An Exploratory Factor Analysis (EFA) on Customer Satisfaction: The Case of McDonald’s Application Users in Bandung City - Mutiarasarry Mulyanti Hidayat; Indra Fajar Alamsyah; Nadia Meirani (Bandung Conference Series: Business and Management, 2024)
Abstract. McDonald's app is a food delivery service offered through a software application that allows customers to enjoy services such as ordering food, finding nearby restaurants, viewing menus, getting promotions, and joining loyalty programs. With this, McDonald's improves customer convenience and experience. The success of the restaurant industry can be measured based on customer satisfaction with McDonald's app. This study uses exploratory factor analysis to identify the components that influence the satisfaction of McDonald's app users in Bandung City. The data used in this study are primary data from respondents in Bandung City who use the McDonald's application or have used it. Factor analysis divides variables into fewer factors. Most of the information about a variable is found in the factors that make it up. The results obtained show that the factors considered in determining user satisfaction with the McDonald's application can be identified using exploratory factor analysis. This is based on the eigenvalue of four factors that have a value of more than one and a cumulative diversity of 65.59%. The factors formed are Service Quality And Customer Satisfaction, Application Quality And Customer Perception, User Experience And User Interface Design, and Information Quality And User Trust. Abstrak. Aplikasi McDonald's adalah layanan pesan-antar makanan yang ditawarkan melalui aplikasi perangkat lunak yang memungkinkan pelanggan menikmati layanan seperti memesan makanan, menemukan restoran terdekat, melihat menu, mendapatkan promosi, dan mengikuti program loyalitas. Dengan ini, McDonald's meningkatkan kenyamanan dan pengalaman pelanggan. Kesuksesan industri restoran dapat diukur berdasarkan kepuasan pelanggan aplikasi McDonald's. Penelitian ini menggunakan analisis faktor eksploratori untuk mengidentifikasi komponen yang mempengaruhi kepuasan pengguna aplikasi McDonald's di Kota Bandung. Data yang digunakan dalam penelitian ini adalah data primer dari responden di Kota Bandung yang menggunakan aplikasi McDonald's atau pernah menggunakannya. Analisis faktor membagi variabel variabel menjadi lebih sedikit faktor. Sebagian besar informasi tentang variabel ditemukan pada faktor yang membentuknya. Hasil yang didapatkan bahwa faktor-faktor yang dipertimbangkan dalam menentukan kepuasan pengguna aplikasi McDonald's dapat diidentifikasi dengan menggunakan analisis faktor eksploratori. Ini didasarkan pada nilai eigen dari empat faktor yang memiliki nilai lebih dari satu dan keragaman kumulatif sebesar 65,59%. Faktor-faktor yang terbentuk yaitu Service Quality And Customer Satisfaction, Application Quality And Customer Perception, User Experience And User Interface Design, dan Information Quality And User Trust.